Kualitas Hidup Pada Pasien Gagal Ginjal Kronik (GGK) - Titin Supriatin; Angella Nur Mustika; Intan Ayu Maharani Putri; Nurkhalifah Khumaeroh; Rizky Adhitya Setiawan; Ridho Fabhio Ramadhan (STIKes Ibnu Sina Ajibarang, 2025)
Chronic kidney disease, commonly abbreviated as CKD, is a condition characterized by a gradual decline in kidney function over a period of three months or more. Between 2018 and 2021, there was a specific increase in cases of kidney failure. According to statistics, 1,602,059 Indonesian residents, including 33,828 in West Java, were affected by kidney failure in 2018. This number is projected to continue rising (Riskesdas, 2020). Globally, the number of End-Stage Renal Disease (ESRD) patients reached 3,200,000 in 2020. Kidney disease typically affects individuals between the ages of 46 and 50. The objective of this literature review is to determine the quality of life of patients with chronic kidney disease (CKD). This review utilized Google Scholar and EBSCO databases, employing keywords such as